Challenges in virtual collaboration : videoconferencing, audioconferencing, and computer-mediated communications - Wainfan, Lynne (Rand Corporation monograph series., 2004)
This report summarizes the research literature on virtual collaboration, focusing on interactive virtual collaborations in real or near-real time. In particular, it reviews how the processes and outcomes of virtual collaborations are affected by the communication medium (videoconferencing, audioconferencing, or computer-mediated conferencing). It then discusses how problems in such collaboration can be mitigated and opportunities realized. Problems include increased "us vs. them" divisions and misunderstandings, as well as shifts toward risky options. Opportunities include broadening the range of views and options, as well as broadening the range of available experts. The report suggests a strategy for choosing the most effective medium, including face-to-face communication and hybrid systems, as a function of task and context (e.g., convergence on a decision or brainstorming)